Politik Hukum Pengelolaan Zakat Di Indonesia - Muhammad Ramli (Universitas Islam Indonesia, 2021)
This study aims to identify and describe: first, the legal politics of zakat management in Indonesia to alleviate poverty; second, the formulation of zakat management in Indonesia to alleviate poverty. This is a normative juridical research type. The results of this study conclude that first, the legal politics of zakat management in Indonesia through the law on zakat management fails to support the national zakat structure which encourages acceleration of poverty alleviation and improvement of welfare and is oriented towards making people who are entitled to receive zakat turn into people who are obliged to pay zakat based on increase in zakat funds collected. Second, the formulation of zakat management in Indonesia is included in the category of partial model or voluntary system, where the state already has a legal basis or formal rules governing zakat, but has not made zakat an obligation that must be fulfilled by citizens. The formulation of future zakat management must be managed with a comprehensive model.Key Word: Formulation; legal politics; poverty alleviation; zakat managementAbstrakPenelitian ini bertujuan untuk menemukan dan mendeskripsikan tentang: pertama, politik hukum pengelolaan zakat di Indonesia untuk mengentasan kemiskinan; kedua, formulasi pengelolaan zakat di Indonesia untuk mengentasan kemiskinan. Penelitian yang dilakukan adalah jenis penelitian yuridis normatif. Hasil penelitian ini menyimpulkan, pertama, politik hukum pengelolaan zakat di Indonesia melalui undang-undang tentang pengelolaan zakat gagal mendukung struktur zakat nasional yang mendorong akselerasi pengentasan kemiskinan dan peningkatan kesejahteraan serta berorientasi pada menjadikan orang yang berhak menerima zakat berubah menjadi orang yang berkewajiban membayar zakat berdasarkan meningkatnya dana zakat yang terkumpul. Kedua, formulasi pengelolaan zakat di Indonesia masuk dalam kategori model parsial atau voluntary system, dimana negara telah memiliki dasar hukum atau aturan formal yang mengatur zakat, namun belum menjadikan zakat sebagai kewajiban yang harus ditunaikan warga negara. Formulasi pengelolaan zakat masa yang akan datang harus dikelola dengan model komprehensif.Kata Kunci: Politik hukum; formulasi; pengelolaan zakat; pengentasan kemiskinan